Superpower : how to think, act, and perform with less effort and better results - Saeks, Ford, 1961- (John Wiley & Sons, 2012)
A road map to better decision-making and a better life! Do you want more out of your life and your job with less effort and better results? Have you ever felt that there just has to be a better way to get there? If so, you're not alone. Millions of people, just like you, are faced with many challenges in their professional and personal lives on their journey to success. Superpower! takes you on a journey where you'll discover seven principles that will help you solve problems faster, make better decisions, and improve your professional and personal life. Develop the common sense insights and c.